INFRASTRUCTURE, ECONOMIC GROWTH AND INEQUALITY IN INDONESIA LAND BORDERS - Bayu Agung Prasetyo; Dominicus Savio Priyarsono; Sri Mulatsih (Universitas Islam Indonesia, 2013)
AbstractThe purpose of this study is to analyze the impacts of infrastructure on economic growth and inequality in Indonesia land borders. Using static panel data regression and panel two stage least square (2SLS) estimation methods, this study shows that social infrastructure can raise per capita income. The social infrastructures being discussed are number of high schools and number of health facilities. Telecommunication facility can also raise per capita income. In addition, income inequality is found to be positively influenced by income per capita growth and industry sector laborer. It also suggests that infrastructure has indirect relation with income inequality through per capita income.Keywords: Land borders, infrastructure, economic growth, inequalityJEL classification numbers: C23, C36, O15, O40, O53, I30, R11AbstrakTujuan penelitian ini adalah untuk menganalisis dampak infrastruktur terhadap pertumbuhan ekonomi dan ketimpangan di perbatasan darat Indonesia. Menggunakan metode estimasi regresi data panel statis dan panel two stage least square (2SLS), penelitian ini menunjukkan bahwa infrastruktur sosial dapat meningkatkan pendapatan per kapita. Infrastruktur sosial yang dibahas adalah jumlah sekolah tinggi dan jumlah fasilitas kesehatan. Fasilitas telekomunikasi juga dapat meningkatkan pendapatan per kapita. Selain itu, ketimpangan pendapatan ditemukan secara positif dipengaruhi oleh pertumbuhan pendapatan perkapita dan buruh sektor industri. Paper ini juga menunjukkan bahwa infrastruktur memiliki hubungan tidak langsung dengan ketimpangan pendapatan melalui pendapatan per kapita.Keywords: Perbatasan darat, infrastruktur, pertumbuhan ekonomi, ketimpanganJEL classification numbers: C23, C36, O15, O40, O53, I30, R11